Matisse and other Modern Masters : The Elise S. Haas Collection. - Bishop, Janet; Klein, John; Lane, John R. (San Francisco : San Francisco Museum of Modern Art, 1993)
Arp, Hans (Jean) ; Brancusi, Constantin ; Derain, André ; Gris, Juan ; Hartley, Marsden ; Hepworth, Barbara ; Laurens, Henri ; Manet, Edouard ; Marini, Marino ; Masson, Andre ; Matisse, Henri ; Monet, Claude ; Moore, Henry ; Nolde, Emil ; O'Keeffe, Georgia ; Picasso, Pablo ; Rivera, Diego ; Rodin, Auguste ; Rouault, Georges
Matisse and other Modern Masters : The Elise S. Haas Collection, San Francisco Museum of Modern Art, San Francisco, 1993
Engels
boek